How Financial Engineering Can Advance Corporate Strategy - Tufano, P (1996)
Practitioners of a new technical specialty--financial engineering--can help senior managers achieve their companies' objectives. Financial engineering can not only reduce the cost of existing activities but also make possible the development of new products, services, and markets. Peter Tufano presents five case studies that illustrate innovative applications of financial engineering and helps managers determine when such techniques are appropriate. The cases highlight five companies that faced different challenges: Enron Capital & Trade Resources, Tennessee Valley Authority, Rhone-Poulenc, Cemex, and MW Petroleum Corporation. All of them found that traditional approaches were inadequate--the costs or the risks seemed too high. A nontraditional solution, however, required that the companies commit to bearing risks that their customers, employees, or counterparties sought to shed. Without a means of structuring, valuing, and mitigating those risks, the initiatives that the companies pursued seemed doomed to failure. In the end, the innovative approach was made possible by the concepts, tools, and markets of financial engineers. The cases show that collaboration between managers and financial engineers can help create a competitive edge by differentiating products through enhanced price and delivery options, by increasing production capacity with flexible alternatives to capital investment, by changing the risk characteristics of holding stock, or by keeping strategic mergers on track through the creation of win-win situations.